The Role of Social Support in Improving Treatment Compliance in Tuberculosis Patients: A Meta-Analysis - Hendra Dwi Kurniawan; Rizki Aqsyari; Fara Khansa Azizah (Journal of Health Promotion and Behavior, 2025)
Background: Tuberculosis is a disease that requires attention in global health issues. Tuberculosis is a disease with a high mortality rate. Although a cure for tuberculosis has been discovered, the treatment process remains challenging, particularly the length of treatment. Tuberculosis patients often fail to complete their treatment due to the lengthy duration. Support from loved ones and a supportive environment is crucial for tuberculosis patients during their treatment. With this support, tuberculosis patients will have a support system that can assist them in their treatment. This study aims to estimate the effect of social support on treatment compliance in tuberculosis patients. Subjects and Method: This study used a systematic review and meta-analysis using PICO. Population: tuberculosis patients. Intervention: social support. Comparison: no social support. Outcome: treatment adherence. The articles used in this study came from 2 databases, namely Google Scholar and Science Direct. The keywords of the article are "tuberculosis" AND ("social support" OR "support system") AND ("adherence" OR "compliance") AND "cross sectional" AND "multivariate". This study uses articles published in 2019 to 2025 with full paper articles, cross-sectional study designs, and the magnitude of the Adjusted Odds Ratio relationship. Articles were analyzed using the Review Manager 5.3 application. Results: Eleven cross-sectional studies showed that social support can increase tuberculosis treatment adherence by 1.44 times compared to tuberculosis patients who do not receive social support, and this result is statistically significant (aOR = 1.44; 95% CI = 1.03 to 2.01; p = 0.03). The forest plot also shows high heterogeneity of effect estimates between primary studies I2 = 84%. The calculation of the average effect estimate was carried out using the random effect model approach. Conclusion: Good social support can help improve treatment adherence in patients with tuberculosis.